The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijerph18137174
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Tooth Loss in Patients with ≥25 Remaining Teeth Undergoing Mid-Long-Term Maintenance: A Retrospective Study

Abstract: Tooth loss represents a diffused pathologic condition affecting the worldwide population. Risk factors have been identified in both general features (smoking, diabetes, economic status) and local tooth-related factors (caries, periodontitis). In this retrospective study, we examined the data of 366 patients with a large number of remaining teeth (≥25) undergoing maintenance therapy in order to identify specific risk factors for tooth loss. The number of remaining teeth, number of non-vital teeth, and number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Other studies reported molar loss in general, which may have been extracted owing to the presence of apical lesions, root fractures or prosthodontic considerations, in addition to periodontal reasons. Endodontically treated molars tend to increase the endodontium‐related risk of loss (Kato et al, 2021; Kawahara et al, 2021). None of the included studies reported data on combined endo‐periodontal lesions, the clinical diagnosis and treatment of which continue to pose a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported molar loss in general, which may have been extracted owing to the presence of apical lesions, root fractures or prosthodontic considerations, in addition to periodontal reasons. Endodontically treated molars tend to increase the endodontium‐related risk of loss (Kato et al, 2021; Kawahara et al, 2021). None of the included studies reported data on combined endo‐periodontal lesions, the clinical diagnosis and treatment of which continue to pose a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Tooth loss is a common oral disease that is more common in the elderly population and is associated with age, smoking, economic status, poor diet, and various oral pathological factors ( 21 ). Evidence shows that tooth loss is related to oral health and cognitive function.…”
Section: Tooth Loss and Cognitive Dysfunctionmentioning
confidence: 99%